MIND MAP DALAM PEMBELAJARAN KETRAMPILAN MEMBACA ‎PEMAHAMAN TEKS BAHASA ARAB ‎ - Azizah, Fithria Rifatul (Program studi Pendidikan Bahasa Arab UNNES, 2020)
Arabic is a scientific discipline consisting of various aspects of the main skills. One skill that is difficult for students to learn is reading skills or reading comprehension. And mind map is the right learning media to help students improve their reading comprehension skills. This research is a qualitative research, the author analyzes findings from interviews, observations and theories obtained previously. This research was conducted in class VII A MTs 9 of Ngawi. The data collection techniques consist of interviews and observations. The purpose of this study is to determine the role of mind map as a media for learning Arabic in improving the comprehension ability of Arabic texts. The results of this study is, 1). Mind map has a significant influence as a method and the right learning media to improve reading skills in understanding Arabic texts, 2) Students feel motivated and more enthusiastic in learning Arabic, 3) Students find it easier to learn to read with their friends 4 ) Students are easier to understand Arabic texts because they have direct experience. Keywords: Mind Map, Reading Comprehension, Learning Media